Clinical efficacy and safety of different tacrolimus concentrations for the treatment of patients with idiopathic membranous nephropathy - Qi Wang (Nature Portfolio, 2021)
Abstract This retrospective study aimed to explore the relative efficacy and safety of different tacrolimus (TAC) concentrations in the treatment of patients with idiopathic membranous nephropathy (IMN). A total of 260 IMN patients with nephrotic syndrome (NS) were recruited. Among these, 125 patients had TAC concentrations no greater than 5 ng/ml (CTAC ≤ 5 ng/ml), and 135 patients had TAC concentrations greater than 5 ng/ml (CTAC > 5 ng/ml). The primary outcomes included complete remission (CR) rates and overall (OR) response rates. The secondary outcomes included 24-h urinary protein (24-h UP), serum albumin and serum creatinine, and adverse events (AEs). During the 12-month follow-up, the overall response rates were significantly different between the CTAC ≤ 5 ng/ml group and the CTAC > 5 ng/ml group (P < 0.0001). However, there was no significant difference in the CR at 12 months between the two groups (chi-square, 62% vs 63%, P = 0.852). Compared with the CTAC ≤ 5 ng/ml group, the CTAC > 5 ng/ml group had improved levels of 24 h UP (P = 0.017) and serum albumin (P = 0.010). Moreover, the incidences of acute reversible nephrotoxicity (P < 0.001), hepatotoxicity (P = 0.036), new-onset diabetes mellitus (P = 0.036), and glucose intolerance (P = 0.005) were lower in the CTAC ≤ 5 ng/ml group than in the CTAC > 5 ng/ml group. The CTAC > 5 ng/ml group was improved relative to the CTAC ≤ 5 ng/ml group in terms of a PR and CR at 6 months, but there was no difference in the CR between the two groups at 12 months.